Synthesis and characterization of (pyrazolylethylphosphinite)nickel(II) complexes and catalytic activity towards ethylene oligomerization. (29th September 2017) - Edor, Juliana M.; Amenuvor, Gershon; Obuah, Collins; Muller, Alfred; Darkwa, James
Abstract : Compounds (2‐(3, 5‐dimethyl‐1 H ‐pyrazol‐1‐yl)ethyldiphenylphosphinite (L1 ), 2‐(3, 5‐di‐tert‐butyl‐1 H ‐pyrazol‐1‐yl)ethyldiphenylphosphinite (L2 ), and 2‐(3, 5‐diphenyl‐1 H ‐pyrazol‐1‐yl)ethyldiphenylphosphinite (L3 ) were prepared using the synthetic routes reported in literature. These compounds were reacted with [NiCl2 (DME)2 ] or [NiBr2 (DME)2 ] under appropriate reaction conditions to afford six new nickel(II) compounds ([NiCl2 (L1)] (1 ), [NiCl2 (L2 )] (2 ), [NiCl2 (L3 )] (3 ), [NiBr2 (L1 )] (4 ), [NiBr2 (L2 )] (5 ) and [NiBr2 (L3 )] (6 )). The new nickel(II) pre‐catalysts catalyze the oligomerization of ethylene, in the presence of ethylaluminium dichloride as co‐catalyst, to produce butenes, hexenes, octenes and higher carbon chain ethylene oligomers with very little Friedel‐Crafts alkylation products when the reactions were run in toluene. Abstract : Pyrazolylphosphinite nickel(II) pre‐catalysts when activation with ethylaluminum dichloride in the presence of ethylene produce C4 ‐C8 and higher carbon content oligomers.